Blood glucose as a predictor of diarrheal dehydration in children - Chandra, Surabhi; Singh, D K; Ansari, Mohd Ayub; Pareek, Prince (Indian Journal of Child Health, 2016)
Background: Diarrhea remains the second leading cause of death globally among under 5 children. Historical clinical characteristics may not correlate to dehydration severity. Objectives: This study was done to evaluate the glycemic status of children having acute diarrhea with dehydration, at presentation, and to analyze the blood glucose as a predictor of the severity of diarrheal dehydration. Materials and Methods: Blood glucose levels were assessed in 150 children with acute diarrhea with dehydration, on admission. Results: Blood glucose levels showed statistically significant association with the degree of dehydration (p<0.05). Receiver operating characteristic curve analysis showed that blood glucose was a poor predictor of the severity of dehydration (area under curve [AUC] 0.240, 95% confidence interval [CI] = 0.050-0.429, standard error [SE] = 0.097) for some dehydration; and (AUC = 0.760, 95% CI = 0.571-0.950, SE = 0.097) for severe dehydration. Conclusion: Blood glucose is a poor predictor of the severity of diarrheal dehydration.